PRACTICE OF WOMEN AGED 25-49 YEARS IN RELATION TO CERVICAL CANCER SCREENING IN ENTEBBE MUNICIPALITY, WAKISO DISTRICT, UGANDA. A CROSS-SECTIONAL STUDY. - Denis Nsubuga; Maureen Andinda; Wilber Ssembajjwe; David Serunjogi (Student's Journal of Health Research, 2023)
Background: Cervical cancer is the most common cancer among Ugandan women of reproductive age. Unfortunately, despite the evidence of methods for prevention, most of the women remain unscreened. In addition, current estimates indicate that 6,413 Ugandan women are diagnosed annually with 4301 deaths. The main purpose of this study was to investigate practice in relation to Cervical Cancer Screening among women aged between 25-49 years in Entebbe Municipality, Wakiso district. Method:  This descriptive cross-sectional study assessed practices in relation to Cervical Cancer screening among women aged between 25-49 years in Entebbe Municipality, Wakiso District; Proportionate sampling was used to select 246 participants from each division for interviews. Interviewer administered questionnaire was used to collect data from the study participants. Collected data was cleaned, coded, and entered in MS Excel spreadsheet 2013 and it was then exported to EPI- INFO Version 7 statistical software for Windows for analysis. The study findings were then presented using tables, graphs, and charts Results:  Only 17.07% of Women in Entebbe Municipality had screened for Cervical Cancer. 76.7% screened only once, 38.88% screened because of awareness that is created, and 30% screened during outreaches. Conclusion:  Cervical cancer screening is still low among women in Entebbe Municipality thus leading to poor actual practice. Recommendation: There is a need to further educate women and the general public on the availability and need for Cervical Cancer screening.